Perbandingan Metode SAW dan TOPSIS dalam Pemilihan Lokasi Restoran Cepat Saji di Cepu - Adhika Pramita Widyassari (JIIFKOM (Jurnal Ilmiah Informatika dan Komputer), 2022)
The increase in population in Indonesia has led to the development of increasingly diverse consumer needs. One of them is the consumer's need for fast food and the increasing mobility of people who want instant goods. Fast food restaurants are one of the fast food industries that are growing rapidly at this time. The many choices of fast food restaurants in Cepu City make consumers have to be observant in choosing which place is the best with various criteria that will be used as a reference. The results of the analysis and data processing obtained the preference value of each alternative. This research was conducted so that consumers can get a restaurant according to their wishes and criteria. From the test results using microst excel, the SAW and TOPSIS methods are equally applicable in this study and based on the calculation results, both SAW and TOPSIS both produce the best restaurant that falls on Crush Chicken.